A revised contact stiffness model of rough curved surfaces based on the length scale. (December 2021) - Yu, Xin; Sun, Yunyun; Zhao, Deng; Wu, Shijing
Abstract: Based on the continuity of length scale for asperities, a complete model of normal stiffness between curved fractal surfaces considering friction factor is proposed. Through the coupling of critical base diameter and contact area, deformation modes of all asperities are determined, and contact stiffness of the whole rough surface is derived by double integral. Accordingly, effects of contact load, surface topography, friction factor, size parameters and material properties on the contact stiffness are investigated. Results show that contact stiffness depends sensitively on the fractal dimension, and exhibits nonmonotonic characteristics as fractal roughness varies across scales. Finally, predicted values of normal stiffness are compared with existing contact models as well as experimental data. Graphical Abstract: ga1 Highlights: A revised contact model between curved friction surfaces is proposed based on continuous length scales. The proposed critical length scales are inherent properties of fractal surfaces. Deformation modes of asperities are determined by incorporating the critical length scale and contact area simultaneously. The relationship of stiffness and fractal roughness shows nonmonotonic across scales and the turning point is affected by the fractal dimension.